NUMERICAL INVESTIGATION OF THE EFFECT ON FOUR BOW DESIGNS FLAT HULL SHIP - Rahmat Azis Nabawi; Syahril (GEOMATE Journal, 2019)
Flat hull ship has some advantages in the manufacturing aspect which are relatively easy to fabricate and does not require high technology equipment. This ship has a weakness where the resistance of flat hull ship is bigger than the other ships among streamlined bow. A factor that influences the ship resistance is the type of bow. So, this study is needed to investigate the effects of bow design and ship resistance. This study aims to reveal the influence of various bows design on resistance and speed of flat hull ship. This study method is numerical analysis using Maxsurf software. The analysis was carried out on four types of bow direction for flat plate hull types, namely Raked Bow, Maier Form, Raked Bow II, and Plumb Bow. The result shows that the flat hull ship with the Raked Bow had the lowest resistance and power. Meanwhile, the flat hull ship with raked bow II had the highest resistance. These results can be a guide for the shipping industry on development and production, and for other researchers in developing the flat hull ship.